Intraosseous Neurilemmoma of the Mandible - Nakasato, Tatsuhiko; Katoh, Kenichi; Ehara, Shigeru; Tamakawa, Yoshiharu; Hoshino, Masayuki; Izumizawa, Mitsuru; Sakamaki, Kimio; Fukuta, Yoshiyasu; Kudoh, Keigo (American Journal of Neuroradiology, 2000)
Summary: We report a rare case of intraosseous neurilemmoma of the mandible, with an emphasis on radiographic findings. The tumor, located mainly in the premolar region, presented as an expansive, unilocular, well-defined, radiolucent lesion on plain radiography. No dilatation of the mandibular canal was identified. MR imaging helped to identify the solid nature of the tumor. A biopsy was necessary to make the final diagnosis because of the relatively nonspecific nature of the lesion.